A Prospective Study of Alcohol Use Patterns and Short‐Term Weight Change in College Freshmen. (8th April 2019) - Fazzino, Tera L.; Forbush, Kelsie; Sullivan, Debra; Befort, Christie A.
Abstract : Background: The transition to college is a developmentally sensitive time in which freshmen are at high risk for engaging in heavy drinking and experiencing changes in weight and body composition. The study tested prospective associations among drinking patterns (weekly drinks, heavy drinking occasions/month) and alcohol calorie intake on weight and waist circumference change over the first year of college. Methods: College freshmen ( N  = 103) were randomly selected from a pool of eligible students to participate at the beginning of the academic year. The sample was comprised of 52% males, 46% of individuals identifying as racial or ethnic minority, and 45% students with at‐risk drinking as defined by the Alcohol Use Disorders Identification Test—Consumption questions. Students engaging in daily risky drinking ( n  = 2) were excluded. Participants attended 3 visits during the academic year during which they provided weight and waist circumference measurements and completed assessments about drinking, dietary intake, and physical activity. Results: Weight gain (>2.3 kg) occurred in 28% of participants. In linear mixed models, drinking patterns and alcohol calorie intake were not associated with weight or waist circumference changes within individuals, when controlling for demographic and energy balance variables. Drinking patterns and alcohol calorie intake did not account for differences in anthropometric measurements between participants, when controlling for covariates. Conclusions: Alcohol use did not explain the anthropometric changes observed in a sample well represented by freshmen engaging in risky drinking (and excluding those with daily risky drinking) during the academic year. Drinking may not contribute to short‐term weight gain among freshmen. Abstract : The transition to college is a developmentally sensitive time in which freshmen are at high‐risk for engaging in heavy drinking and experiencing changes in weight and body composition. The study prospectively tested the relationship between alcohol use patterns and short‐term weight and waist circumference change in a sample of college freshmen well‐represented across sex, race/ethnicity, and at‐risk drinking status.